Examining of the Relationship between Family Quality of Life, Parenting Stress and Marital Life Satisfaction of Mothers with Children with Special Needs - Zeynep Çam Alegöz; Halil İbrahim Sağlam (Sakarya University Journal of Education)
This study was conducted to examine the relationship between family quality of life, parenting stress and marital life satisfaction of mothers with children with special needs in early childhood. A total of 212 mothers with children with special needs aged 0-8 years participated in the study. The data were collected with "Personal Information Form", "Beach Centre Family Quality of Life Scale", "Parenting Stress Scale" and "Marital Life Satisfaction Scale". As a result of the study, it was determined that there was a negative and significant relationship between marital life satisfaction and parenting stress levels of mothers with children with special needs; a positive and significant relationship between marital life satisfaction and family life quality; and a negative and significant relationship between family life quality and parenting stress levels. In the study, it was concluded that family quality of life differed significantly in favor of working mothers according to their employment status; it did not differ significantly according to the age and education level of the mother. It was determined that the parenting stress of mothers differed significantly in favor of university graduates in the comparison of university graduates with secondary and high school graduates according to their educational levels; it did not differ significantly according to the age and working status of the mothers. It was concluded that marital life satisfaction of mothers differed significantly in favor of mothers in the 20-29 age range according to the age of the mothers; it did not differ significantly according to the mother's education level and employment status. The findings are discussed in the light of the literature and suggestions for further research are given.